The herbal pharmacopoeia of Ecuador: a national model for integrating traditional knowledge and biodiscovery - Llivisaca-Contreras, Susana; Naranjo-Morán, Jaime; Bastidas-Gálvez, Martín; Jaime-Carvajal, Jairo; Muenala-Tituaña, María; Manzano-Santana, Patricia; Abad-Mihalache, Adrián; Abril-Novillo, Andrea; Cevallos-Cevallos, Juan M.; Orellana-Manzano, Andrea; León-Tamariz, Fabián (Frontiers in Pharmacology, 2025)
IntroductionThe Herbal Pharmacopoeia of Ecuador is a proposal aimed at systematizing and organizing information on the use of medicinal plants and natural products through the scientific evaluation of existing knowledge (ancestral or otherwise) in Ecuador, a country with high biodiversity and a rich ethnobotanical heritage, contributing to the safe use of medicinal plants and their potential phytopharmaceutical derivatives, offering safe alternatives for the treatment or relief of various health conditions.ObjectivesTo build a foundation that organizes and structures validated information on medicinal plants and natural products, serving in the future as a reference resource for the development of phytotherapeutic products, knowledge transfer, protection of ancestral knowledge, supported by regulatory bodies, and as a source of consultation for health professionals in Ecuador.MethodologyAn interdisciplinary approach was used to develop monographs on medicinal plants used in various regions of Ecuador, integrating an extensive literature review that highlights ethnobotanical, pharmacological, and phytochemical analysis. In a collaborative effort by academic institutions integrated into the VLIR-Ecuador Network, a digital platform was developed using the Angular software framework to organize these monographs.ResultsThe creation of a digital platform enabled the systematization of scientific knowledge on 14 selected medicinal plants through the generation of monographs, organized within the Ecuadorian Herbal Pharmacopoeia. This has facilitated access for the medical and scientific community to relevant data on the common use of plants and traditional Ecuadorian medicine.ConclusionThe official adoption of an Herbal Pharmacopoeia in Ecuador will strengthen scientific production, support the regulation of natural products, protect ancestral knowledge, and promote research on bioactive compounds. Its success will depend on collaboration between the government, academia, industry, and ancestral communities, ensuring its development and positioning Ecuador as a leading reference in ethnobotany and biosustainability.